Integrating family planning services into HIV care: use of a point-of-care electronic medical record system in Lilongwe, Malawi. Issue 1 (1st January 2017) - Tweya, Hannock; Feldacker, Caryl; Haddad, Lisa B.; Munthali, Chimango; Bwanali, Mwatha; Speight, Colin; Kachere, Layout G.; Tembo, Petros; Phiri, Sam
ABSTRACT: Background : Integrating family planning (FP) services into human immunodeficiency virus (HIV) clinical care helps improve access to contraceptives for women living with HIV. However, high patient volumes may limit providers' ability to counsel women about pregnancy risks and contraceptive options. Objectives : To assess trends in the use of contraceptive methods after implementing an  electronic medical record (EMR) system with FP questions and determine the reasons for non-use of contraceptives among women of reproductive age (15–49 years) receiving antiretroviral therapy (ART) at the Martin Preuss Center clinic in Malawi. Methods : In February 2012, two FP questions were incorporated into the ART EMR system ( initial FP EMR module) to prompt providers to offer contraceptives to women. In July 2013, additional questions were added to the FP EMR module ( enhanced FP EMR) to prompt providers to assess risks of unintended pregnancies, solicit reasons for non-use of contraceptives and offer contraceptives to non-pregnant women . We conducted a retrospective, longitudinal cohort study using the EMR routinely collected data. The primary outcome was the use of any modern contraceptive method. Descriptive statistics were used to describe the study population and report trends in contraceptive use during the initial and enhanced study periods. Results : Between February 2012 and December 2016, in HIV clinics, 20, 253 women of reproductive age received ART, resulting in 163, 325 clinic visits observations. The proportion of women using contraceptives increased significantly from 18% to 39% between February 2012 and June 2013, and from 39% to 67% between July 2013 and December 2016 (chi-square for trend p < 0.001). Common reasons reported for the non-use of contraceptives among those at risk of unintended pregnancy were: pregnancy ambivalence (n = 234, 51%) and never thought about it (n = 133, 29%). Conclusion : Incorporating the FP EMR module into HIV clinical care prompted healthcare workers to encourage the use of contraceptives.